The Effect of Compost and Fly Ash Treatment of Contaminated Soil on the Immobilisation and Bioavailability of Lead - Monika Jakubus; Małgorzata Graczyk (Agronomy, 2021)
The study discusses changes in lead contents in soil and crops after application of compost and fly ash. A three-year experiment was conducted on narrow-leaved lupine (Lupinus angustifolius L.), camelina (Camelina sativa L.) and oat (Avena sativa L.), which were grown on medium soil fertilised with compost or fly ash (FA). The lead amounts in various combinations were evaluated using sequential (BCR analysis) and single (DTPA solution) methods. The total contents of lead and amounts of selected macronutrients were assessed in the biomass of plants. The Pb contents in the soil and plants were used to calculate the risk assessment code (RAC), individual contamination factor (ICF), bioconcentration factor (BCF) and contamination coefficient level (CCL). Lower amounts of bioavailable Pb in the soil were observed as a result of compost and FA application. Fly ash immobilised Pb more effectively, as evidenced by the BCF and CCL values. The increase in the Pb contents in the sequentially separated fractions and in plant biomass were caused by applied compost or FA. The Pb contents in exchangeable forms decreased, whereas its contents in residual forms increased.